Kualitas Audit pada KAP di Kota Malang: Peran Independensi, Kompetensi, dan Budaya Organisasi - Aprillia Dwi Lestari; Muhammad Dimar Alam (As-Syirkah: Islamic Economic & Financial Journal, 2026)
This study aims to obtain empirical evidence that independence, competence, and organizational culture have a positive effect on audit quality. This quantitative study uses primary data obtained from questionnaires distributed to respondents selected through convenience sampling from the population of auditors at public accounting firms in Malang City. Data analysis and hypothesis testing were conducted using SEM-PLS. This study finds that independence and competence have a positive effect on audit quality at public accounting firms in Malang City, while organizational culture has no significant effect. These findings are expected to provide empirical evidence supporting attribution theory, which highlights the influence of auditors’ internal and external factors on audit quality.